Seroprevalence of hepatitis C virus antibodies among Sudanese patients with schistosomiasis referred to Al-elafon military hospital in Khartoum state - Mohamed Bashir Hussein Faruha; Rasha Zienalabdeen; Babbiker Mohammed Taher Gorish; Mohamed Abdalrahim Ahmed Abdelgalil; Mohamed Ali Siddig Ali; Omer Abdalgadir Ahmed Taha; Sara Abdalhakam Yousif Elterafi; Walla Abdalgfar Albushra Mohamed (Journal of Medical and Scientific Research, 2019)
Background: Hepatitis C virus (HCV) infection and schistosomiasis, has worldwide coexistence especially in Africa. Some researchers suggest that schistosomiasis is the risk factor for the development of HCV infection.